The Effect of Green Tea on the Expression of NPC1L1, ABCG5, and ABCG8 in the Intestine of High Fat Diets-induced Rats - Erna Susanti; Endang Susilowati (The Prodia Education and Research Institute (PERI), 2021)
BACKGROUND: Signaling pathways contributing to cholesterol efflux and inhibitory inflammation in atherosclerosis that has not been explored is the liver X receptor (LXR). Catechin as LXR agonist influences the expression of Niemann-pick C1 like 1 (NPC1L1) protein transporter that triggers the inhibition of cholesterol absorption. This study aimed to examine the effect of Catechins on the expression of intestinal transporters: NPC1L1, ATP-binding cassete-proteins G5 (ABCG5) and G8 (ABCG8).METHODS: Twenty-five experimental animals were divided into five treatment groups, with 5 rats in each group. The groups were normal diet rats (group 1), high fat diets-induced rats (group 2), high fat diets-induced rats treated with 30 mg/kg body weight (BW) of Catechins (group 3), high fat diets-induced rats treated with 60 mg/kg BW of Catechins (group 4), and high fat diets-induced rats treated with 120 mg/kg BW of Catechins (group 5). After one-month, all rats were sacrificed, blood and intestine were collected. Lipid profile were determined enzymatically, mRNA levels were determined by reversetranscriptase polymerase chain reaction (RT-PCR), while the expression of protein transporter were determined by immunohistochemistry.RESULTS: Catechins treatment decreased the expression of NPC1L1, but increased the expression of ABCG5 and ABG8.CONCLUSION: Catechins can be developed as a candidate for NPC1L1 inhibitor to mediate the inhibiting absorption of intestinal cholesterol, therefore increasing the inhibitory effect of atherogenesis.KEYWORDS: ABCG5, ABCG8, aterogenesis, Catechins, green tea, NPC1L1